HUBUNGAN SELF DIRECTED LEARNING READINESS DENGAN TINGKAT KECEMASAN MAHASISWA TINGKAT PERTAMA TAHUN 2010-2011 FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SURAKARTA - Triastuti, N. Juni (Biomedika, 2013)
The anxiety level can be infl uence learning achievement. While the self directed learning readiness can be infl uence learning achievement. The purpose of this study was to determine wheter self directed learning readiness have relationship with the anxiety level at the fi rst medical education student of University Muhammadiyah Surakarta. This study involve 49 responden that receive kuisioner about self directed learning readiness and kuisioner of Hamilton Anxiety Scale. With Spearman test, , the result of this study show that Sig value of the psyche anxiety is 0.550, physics anxiety 0.260 and general anxiety 0.079. This value indicate that there are not signifi cant relationship between self directed learning readiness and the anxiety level. Based on study result, we concluded that self directed learning readiness didn?t have signifi cant relation with the anxiety level at the fi rst medical education student of University Muhammadiyah Surakarta.Keywords: self directed learning readiness, the anxiety level.